1999
DOI: 10.1016/s0969-2126(99)80057-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the PH domain from Bruton's tyrosine kinase in complex with inositol 1,3,4,5-tetrakisphosphate

Abstract: Our data provide an explanation for the specificity and high affinity of the interaction with phosphatidylinositol 3,4,5-trisphosphate and lead to a classification of the XLA mutations that reside in the Btk PH domain. Mis-sense mutations that do not simply destabilize the PH fold either directly affect the interaction with the phosphates of the lipid head group or change electrostatic properties of the lipid-binding site. One point mutation (Q127H) cannot be explained by these facts, suggesting that the PH do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
227
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(236 citation statements)
references
References 71 publications
(98 reference statements)
7
227
0
2
Order By: Relevance
“…In addition, a chimeric protein containing the PH-TH module of Btk artificially fused to the kinase domain of c-Abl is also activated by IP 6 . Second, crystal structures of the PH-TH domain ( Figure 1C) reveal a dimeric structure (referred to as the Saraste dimer, as it was first identified by Matte Saraste and colleagues) (Baraldi et al, 1999b;Hyvonen and Saraste, 1997), and mutation of residues at this dimer interface prevents activation by IP 6 in solution (Wang et al, 2015). These observations led to the hypothesis that there is a transient dimerization promoted by IP 6, and that it is important in Btk activation.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, a chimeric protein containing the PH-TH module of Btk artificially fused to the kinase domain of c-Abl is also activated by IP 6 . Second, crystal structures of the PH-TH domain ( Figure 1C) reveal a dimeric structure (referred to as the Saraste dimer, as it was first identified by Matte Saraste and colleagues) (Baraldi et al, 1999b;Hyvonen and Saraste, 1997), and mutation of residues at this dimer interface prevents activation by IP 6 in solution (Wang et al, 2015). These observations led to the hypothesis that there is a transient dimerization promoted by IP 6, and that it is important in Btk activation.…”
Section: Introductionmentioning
confidence: 83%
“…The other is a secondary inositol phosphate binding site, referred to here as the peripheral site, that is proximal to the Saraste dimer interface ( Figure 1B). Mutations at the peripheral binding site prevent the activation by IP 6 of Btk, as well as the Btk-Abl chimera (Wang et al, 2015), suggesting that the occupation of the peripheral site by an inositol phosphate may allosterically influence the ability of the PH-TH module to dimerize (Baraldi et al, 1999a). However, dimerization of the Btk PH-TH module in solution has not been detected directly, with or without IP 6 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the finding in the present study that PH domains possessing a perfect or near-perfect PPBM consensus do not always interact with PtdIns(3,4,5)P $ specifically emphasizes that residues lying outside the PPBM also influence the interaction of many PH domains with phosphoinositides. Structural studies also show that residues lying outside of the PPBM also form direct contacts with the inositol phosphate moieties of phosphoinositides [2,13,20]. Previous studies have demonstrated that phospholipase Cδ " , which also possesses a PPBM, does not bind to PtdIns(3,4,5)P $ with a high affinity [20].…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of certain of the conserved residues in the PPBM in some PH domains has been shown to abolish interaction with PtdIns(3,4,5)P $ [11]. Recent structural studies of the PH domain of BTK bound to the head group of PtdIns(3,4,5)P $ indicate that the basic amino acids in the PPBM may form direct interactions with the monoester phosphate groups of PtdIns(3,4,5)P $ [2,12,13]. To identify novel proteins that interact with PtdIns(3,4,5)P $ , we searched expressed sequence tag (EST) databases for proteins possessing a PH domain containing a PPBM.…”
Section: Introductionmentioning
confidence: 99%
“…[109][110][111] Recruitment of btk to the cellular membrane and its subsequent activation triggers the mobilization of intracellular calcium and the activation of PKC, resulting in the degradation of the NFkB inhibitory protein I-kBa and the translocation of NF-kB to the nucleus. [112][113][114] In humans, more than 175 different mutations involving all domains of the btk gene have been identified in XLA patients. 102 In xid mice, a missense mutation at a conserved arginine residue (R28C) within the PH domain of btk impairs its ability to translocate to the plasma membrane and trigger signaling cascades that regulate B-cell survival and growth, 101,105,111 consequently affecting resistance to infection with Salmonella.…”
Section: Tlr4mentioning
confidence: 99%